The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1039/c9cp05390e
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency spin filtering in magnetic phosphorene

Abstract: We present high efficiency spin filtering behaviour in magnetically rendered phosphorene, doped with various 3d block elements. A phase diagram was obtained depicting the presence of various electronic and magnetic states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…In addition, van der Waals heterostructure of these 2D materials can be employed to generate engineered properties for desired applications. 12 The presence of spontaneous magnetism in 2D materials could effectively pave its way in spintronics, 13 which was however limited to the observation of edge-magnetism or vacancy/doping induced magnetism, 14 localised in nature. To establish a long range magnetic ordering (LRMO) in two-dimension, anisotropy is required to establish an energy gap in the spin wave spectrum, overcoming the thermally induced magnon excitation, as theoretically predicted through Onsager's model 15 and Mermin–Wagner–Hohenberg theorem.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, van der Waals heterostructure of these 2D materials can be employed to generate engineered properties for desired applications. 12 The presence of spontaneous magnetism in 2D materials could effectively pave its way in spintronics, 13 which was however limited to the observation of edge-magnetism or vacancy/doping induced magnetism, 14 localised in nature. To establish a long range magnetic ordering (LRMO) in two-dimension, anisotropy is required to establish an energy gap in the spin wave spectrum, overcoming the thermally induced magnon excitation, as theoretically predicted through Onsager's model 15 and Mermin–Wagner–Hohenberg theorem.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in Δ3 is understood by seeing that the CBM has higher energy in LL-Cys than in the OH-functionalized system, 0.77 eV for the former against 0.61 eV for the latter (see Figure S6). Kumari et al reported magnetic properties of phosphorene after doping with different metals from the 3D block and, between the different resulting classes of magnetic materials, they found that phosphorene develops in-gap states with values of Δ2 and Δ3 suited enough for potential applications as BMS …”
Section: Results and Discussionmentioning
confidence: 99%
“…This represents an alternative approach to induce a magnetic structure in a nonmagnetic system without doping with metallic atoms. 52 In Figure 2d, we show the spin-resolved electronic band structure of the 1-OH system. The first feature to notice is the appearance of in-gap electronic bands with weak dispersion, a result of the altered local structure of the phosphorene layer at the functionalization sites, which effectively acts as a nearly localized structural defect.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…which have sparked their immense applications in diverse fields of electronics, optics, optoelectronics and memory devices [1][2][3] etc. Most of these materials are non-magnetic and according to Mermin-Wagner theorem [4,5], the presence of long-range magnetic ordering in 2D materials is not possible due to thermal fluctuations [6,7]. Despite this, recently several intrinsically magnetic 2D materials have been discovered [8] with finite critical temperature ( T c ), like CrI 3 [9], Cr 2 Ge 2 Se 6 [10], and Cr 2 Ge 2 Te 6 [11,12].…”
Section: Introductionmentioning
confidence: 99%